FAMILY TACHINIDAE - Nihei, Silvio S. (Zootaxa, 2016)
The present catalogue summarizes 154 species and 71 genera occurring in Colombia. All the four subfamilies (Phasiinae, Dexiinae, Tachininae and Exoristinae), and 24 tribes are represented in the Colombian territory.